The role of diet and antioxidants in the prevention of Alzheimer’s disease - Dudkowiak, Robert; Gryglas, Anna; Poniewierka, Elżbieta (Journal of Medical Science, 2016)
Alzheimer’s disease (AD) is the most common form of dementia among elderly. It is a progressive, neurodegenerative disorder of the brain which leads to the deterioration of cognitive, behavioral and impaired daily functioning and causes the gradual loss of independence. A significant portion of risk for dementia in old age is associated with lifestyle. Three important protective factors are diet, which should be rich in antioxidants, exercise and good cardiovascular health. It is believed that Mediterranean diet has a protective effect from dementia. This diet, rich in fruit and vegetables, legumes, olive oil, whole wheat bread, fish and seafood, with reduced consumption of red meat is also protective from cardiovascular diseases and promotes a healthy long life. There were some studies on the etiology of AD which noted an important role of vitamin B6, B12 and folic acid. All of them are involved in the metabolism of homocysteine, which is regarded as an independent risk factor for the development of AD, atherosclerosis and thrombosis. We also know that supplementation of vitamins C and E in the diet can be protective from AD. On the other hand we know that obesity and undernutrition can increase the risk of development of AD. As we can observe the aging of population we should remember that nutrition constitutes an interesting approach for the prevention of age-related brain disorders.